A system dynamics model analysis for policy impacts on green agriculture development: A case of the Sichuan Tibetan Area. (15th October 2022) - Wang, Wenke; Li, Kang; Liu, Yang; Lian, Jiayao; Hong, Shu
Abstract: Tibetan area of Sichuan Province is the green shelter for national ecological security, so the local agriculture should follow the path of green development rather than the traditional way. To develop green agriculture, proper policies need to be put forward. Therefore, it is necessary to simulate and test the policies proposed and see the long-term outcomes of implementing each policy before making the final decisions. The system dynamics model is a suitable way to simulate the impact of various policies on the development of green agriculture in the Sichuan Tibetan area from a dynamic and systematic perspective. Unlike existing studies that only consider unilateral policy impact, this paper conducts policy simulations from multiple aspects of population, investment and ecological environment. The simulation results showed that population policy and investment policy had a significant effect on improving the agricultural economic benefits. The agricultural output value will increase maximum of 2.8% if the population grows by 1.2% and more rural people are engaged in agricultural activities. The grain output will increase maximumly 9.8% if the sown area of crops increases by 1.2% each year and the investment in agricultural fixed assets increases by 2%. Green policy played a significant role in improving the ecological benefits of agriculture, and the maximum relative ratio of the green index of agricultural development was 12.2%. Finally, some suggestions are put forward, including government investment, protection of the agricultural ecological environment, and promotion of the agricultural market. It is anticipated that this system dynamic model and suggestions can contribute to the green development of agriculture in the Sichuan Tibetan area and other areas. Graphical abstract: Image 1 Image 1 Highlights: Sichuan Tibetan area is the green shelter for China's ecological security. Policy plays the most prominent role in green agriculture development. Population and investment policies drive green agricultural economic benefits. Green policy contributes to the ecological benefits of green agriculture.